Ethnic variation of gastroschisis and omphalocele in the United States of America*. (13th January 2014) - Rocha, Frederico G.; Zalud, Ivica; Dye, Timothy
Abstract: Objective : Gastroschisis and omphalocele are the most common fetal abdominal wall defects (AWDs). Ethnic factors have been implicated in the incidence data from some states in the United States. Our aim was to examine ethnic variation in the prevalence of gastroschisis and omphalocele in the US live birth population between 2006 and 2010. Methods : AWDs were identified through gastroschisis and omphalocele checkboxes from publicly available US Natality data (2006 to 2010). Ethnicity was evaluated by individual category using National Center for Health Statistics (NCHS) definitions. Adjusted multinomial logistic regression (SPSS v.19) was used to generate odds ratios (OR) in order to quantify the disparities. Results : In the US, 7867 live births were identified with AWD. All ethnic groups showed a significantly higher OR when compared with women of East/South Asian descent, which experienced the lowest prevalence. Women of indigenous ethnicity had the highest individual OR while their adjusted OR remained greater than 4.0. Conclusions : Women of indigenous origin from North America and the Pacific had the highest rates of AWD. Within this group, women of Hawaiian descent had the highest point estimate of AWD when compared with other ethnic groups, though not significant.